Theory of residual stresses with application to an arterial geometry - Klarbring, A.; Olsson, T.; Stalhand, J. (Archives of Mechanics, 2007)
This paper presents a theory of residual stresses, with applications to biomechanics, especially to arteries. For a hyperelastic material, we use an initial local deformation tensor K as a descriptor of residual strain. This tensor, in general, is not the gradient of a global deformation, and a stress-free reference configuration, denoted B-, therefore, becomes incompatible. Any compatible reference configuration B0 will, in general, be residually stressed. However, when a certain curvature tensor vanishes, there actually exists a compatible and stress-free configuration, and we show that the traditional treatment of residual stresses in arteries, using the opening–angle method, relates to such a situation. Boundary value problems of nonlinear elasticity are preferably formulated on a fixed integration domain. For residually stressed bodies, three such formulations naturally appear: (i) a formulation relating to B0 with a non-Euclidean metric structure; (ii) a formulation relating to B0 with a Euclidean metric structure; and (iii) a formulation relating to the incompatible configuration B-. We state these formulations, show that (i) and (ii) coincide in the incompressible case, and that an extra term appears in a formulation on B-, due to the incompatibility.